Phaeoclavulina liliputiana sp. nov. (Gomphaceae, Gomphales) a new endemic species from Tlaxcala, Mexico - González-Ávila, Astrid; Martínez-González, César Ramiro; Espinosa, David; Estrada-Torres, Arturo (Phytotaxa, 2020)
Phaeoclavulina liliputiana is a new endemic species from Tlaxcala, from the conifer and oak forests at an altitude of 2700 m asl, characterized by a very small basidiome size and, subellipsoid and usually more or less lacrymoid spores of 4.3–6.2 × 2.7–3.5 µm, with rounded warted ornamentation. We proposed this new species based on evidence from morphological and molecular data. We provide macro- and microscopic descriptions including illustrations of the basidiocarp, scanning electron micrographs of the basidiospores and also discuss the taxonomic position of this new species. We undertook a molecular analysis using the atp6 and SSU mitochondrial loci and nuclear ribosomal LSU.